Immunohistochemical detection of the BRAF V600E-mutated protein in papillary thyroid carcinoma - Koperek, Oskar; Capper, David; Bergmeister-Berghoff, Anna Sophie; Deimling, Andreas von (The American journal of surgical pathology, 2012)
The V600E mutation of the B-type Raf kinase (BRAF) gene is a common event in papillary thyroid carcinoma (PTC) and seems to play a key role in the development and progression of this disease. We evaluated the expression of the mutated BRAF V600E protein in 144 cases of PTC using a novel mutation-specific antibody. Seventy-six PTCs (52.8%) showed unequivocal diffuse cytoplasmic expression of the mutated BRAF protein, and the T1799A point mutation was confirmed by sequencing analysis in selected cases. No statistical difference in V600E BRAF protein expression was seen between microcarcinomas and macrocarcinomas. Further, no significant correlation of V600E expression with clinicopathologic parameters of aggressiveness such as lymph node metastasis, peritumoral infiltration, or perithyroidal infiltration was found. BRAF V600E protein expression was significantly more common in tumors with tall cell or oncocytic features but was less common in tumors with follicular growth pattern. Diffuse sclerosing, solid and follicular variants did not show the mutated BRAF protein. Immunohistochemical detection of the mutated V600E BRAF protein in PTC may facilitate mutational analysis in the clinical setting. Our data show that the expression of the mutated BRAF V600 protein and thus the corresponding BRAF mutation seems not to be per se a marker of aggressiveness but is already seen in clinically indolent microcarcinomas. Nevertheless, the investigation of BRAF V600E protein expression might be of clinical interest especially in therapy-resistant disease, as new therapeutics inhibiting the mutated protein are clinically available.
Gesehen am 29.10.2018